1996
DOI: 10.2136/sssaj1996.03615995006000060004x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Ponderosa Pine Site Productivity following Removal of Understory Vegetation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(49 citation statements)
references
References 43 publications
(39 reference statements)
3
45
1
Order By: Relevance
“…In agreement with previous research in temperate forests and subtropical plantation forests, our results indicate that understory plants increase soil water retention, moderate soil temperature and help maintain soil quality (Busse et al 1996. Experiments in boreal forests, in contrast, showed that understory and overstory species compete for nutrients and water (Nilsson and Wardle 2005).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with previous research in temperate forests and subtropical plantation forests, our results indicate that understory plants increase soil water retention, moderate soil temperature and help maintain soil quality (Busse et al 1996. Experiments in boreal forests, in contrast, showed that understory and overstory species compete for nutrients and water (Nilsson and Wardle 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Fire encouraged fire-tolerant tree species and discouraged fire-sensitive species as reported by Ivanauskas et al (2003). Fires may also play a significant role in regulating ecosystem productivity and diversity by promoting mineralization of nutrients stored in organic matter and allowing the invasion of rapid growing early successional species (Busse et al, 1996;DeBano et al, 1998;Boerner et al, 2009). Soil provides numerous essential ecosystem services such as primary production (including agricultural and forestry products); regulation of biogeochemical cycle (with consequences of the climate); water filtration, resistance to diseases and pests and regulation of above ground biodiversity .…”
Section: Introductionmentioning
confidence: 89%
“…5 Measurements of various morphological traits were collected prior to shrub removal, then 6 sapling height growth response was measured periodically after the release treatment. In general, 7 giant sequoia responded quickly to the removal of competing shrubs, growing steadily for 20 8 years following treatment. Among the morphological traits considered, live crown ratio alone 9 was the most important factor in predicting relative height growth following treatment.…”
mentioning
confidence: 99%
“…Maclaren 2004). 8 Closer to its native range consisting of disjunct groves on the western slopes of the Sierra 9…”
mentioning
confidence: 99%
See 1 more Smart Citation